2021
DOI: 10.1371/journal.pone.0256417
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ knowledge of diabetes foot complications and self-management practices in Ghana: A phenomenological study

Abstract: Background The prevalence of diabetes is increasing in low and middle-income countries (LMICs) and over two-thirds of these are not diagnosed. Consequently, diabetes complications usually exist at the time of diagnosis. Foot ulcers is a leading cause of disability and mortality among diabetes patients. Purpose To assess the knowledge and experiences of adult patients with Diabetes on diabetes complications and self-management practices with emphasis on foot care. Methodology This applied phenomenological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…A lack of understanding of diabetes related foot disease and the perceived need for foot care was a common barrier identified by patients that prevented them from accessing foot care services. It has been well-established that patients with diabetes lack knowledge about foot complications and their prevention [33][34][35][36]. A lack of knowledge about one's condition and how it is managed has been shown to cause a low perceived need and reduction in care seeking across many chronic conditions [7].…”
Section: Discussionmentioning
confidence: 99%
“…A lack of understanding of diabetes related foot disease and the perceived need for foot care was a common barrier identified by patients that prevented them from accessing foot care services. It has been well-established that patients with diabetes lack knowledge about foot complications and their prevention [33][34][35][36]. A lack of knowledge about one's condition and how it is managed has been shown to cause a low perceived need and reduction in care seeking across many chronic conditions [7].…”
Section: Discussionmentioning
confidence: 99%
“…These factors allow foot ulcers to progress and become chronic, nonhealing wounds. The inadequate management of underlying factors, such as uncontrolled diabetes and peripheral neuropathy, perpetuates this cycle, resulting in recurrent foot ulcers and an elevated risk of complications 24,25 …”
Section: Dfus In Lmics: Aetiology and Risk Factors Pathophysiology An...mentioning
confidence: 99%
“…A study in Ghana highlighted the significance of diabetic clinics as the primary source of education and understanding about DFUs to reduce diabetes‐related foot complications. 24 Categorizing patients based on risk factors at the primary health care level, particularly by nurses, is crucial for identifying those at risk for ulceration. This approach ensures accessibility to a broader population and is the initial entry point for individuals seeking foot health services.…”
Section: Future Strategies For Reducing Dfu‐related Amputations In Lmicsmentioning
confidence: 99%
“…There is a limited publication on DM self-management in the WHO African region although these studies have reported positive benefits of self-management (Kumah et al , 2021). The limited studies reported in the Ghanaian context places emphases disease management tasks such as foot care, self-care support and adherence to self-care recommendations (Mogre et al , 2019; Kumah et al , 2021; Bossman et al , 2021). However, to date, there does not appear to be any study focusing on people’s attitudes and behaviour around information for self-management for people living with DM.…”
Section: Research Problemmentioning
confidence: 99%